Педагогічні умови і структурно-функціональна модель формування професійної ідентичності майбутніх бакалаврів іноземної мови - Гнатик Каталін; Katalin Hnatyk; Hnatik Katalin; Лізак Катерина; Kateryna Lizak; Lizák Katalin (Видавництво МДУ, 2020)
Резюме. У статті виокремлено сукупність дієвих педагогічних умов і обґрунтовано основні складники структурно-функціональної моделіформування професійної ідентичності майбутніх бакалаврів іноземної мови. Проаналізовано змістове наповнення категорій «умова», «педагогічна умова». Встановлено, щоефективний вплив на процес формування досліджуваного феномену забезпечать такі педагогічні умови: формування позитивного «Я-образу» професіонала у свідомості студентів шляхом використання методу кейсів; забезпечення формування професійного світогляду майбутніх бакалаврів іноземної мови на основі розширення змісту навчальних дисциплін інформацією міждисциплінарного характеру; використання освітнього контексту професійної підготовки майбутніх бакалаврів іноземної мови як середовища для формування професійної ідентичності; організація рефлексивно-творчої навчальної діяльності студентів.

Abstract. The article identifies a set of effective pedagogical conditions and substantiates the main components of the structural and functional model of future bachelors’ professional identity formation in foreign language teaching. The content of the categories "condition" and "pedagogical condition" are analyzed. It is summarized that the common feature of these definitions is the interpretation of pedagogical conditions as factors of positive influence on the course of pedagogical processes or the functioning of pedagogical systems to improve their effectiveness. Under the pedagogical conditions, an interconnected set of internal and external factors, means and measures will be interpreted, which will ensure the high efficiency of the process of forming the professional identity of future bachelors in foreign language teaching. Generally, the pedagogical conditions are distinguished in such a way that their implementation maximally effectively influences the formation of all components of future bachelors’ professional identity. It was assumed that the effective solution of the problem is the quality of the obtained results which will depend on the introduction of appropriate pedagogical conditions in the educational process of institutions of higher education. It is established that the following pedagogical conditions will provide an effective influence on the process of formation of the phenomenon under study: formation of a positive "I-image" as a professional in the mind of students by using the method of cases; ensuring the formation of a professional outlook for future bachelors on the basis of expanding the content of academic disciplines with information of a multidisciplinary nature; the use of the educational context for the training of future foreign language bachelors as a medium for the formation of professional identity; organization of students' reflective and creative educational activity. In order to develop a structural and functional model for the formation of future bachelors’ professional identity the following main components are specified: the purpose, methodological approaches to the formation of future bachelors’ professional identity in foreign language teaching, principles of study, stages, the criteria and levels of future bachelors’ professional identity. The result is a developed structural and functional model presented in the form of interconnected blocks: theoretical, methodological, diagnostic, activity-practical, result-analytical. The author's structural-functional model of forming the future bachelors’ professional identity in foreign language teaching is based on the interrelation of all its structural elements and reflects the complex realization of all the pedagogical conditions defined in the study.
Pedagogical conditions and structural-functional model of future bachelor’s professional identity formation in foreign language teaching
Keywords: педагогічні умови; професійна ідентичність; модель; структурно-функціональна модель; майбутні бакалаври іноземної мови; студенти; pedagogical conditions; professional identity; model; structural and functional model; future bachelors in foreign language teaching; students